Development of conceptual and categorical apparatus of control of NBFIs - Zh.V. Prokopenko (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The article researches the essence of the term «provision of pensions». The author finds out the imperfection of conceptual and categorical apparatus of certain issues leading to the conflict between the interpretations and is the blocking factor for the pension system. The paper reveals that there is no single interpretation of the term «investment», but the suggested definitions are grouped according to the following approaches: investment as input, costs and the definition of investment at the micro and macro levels. A large number of authors define investment as investing in anything for profit. It was found out that the category of «financial leasing» is multifaceted and multifold, but considering it in the context of nonbank financial institutions, it should be noted its significant characteristic, which is a financial service.